Faktor-Faktor yang Mempengaruhi Intellectual Capital - Priscilla Gita; Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence regarding the factors such as profitability, board size, and institutional ownership that affect intellectual capital in manufacturing companies listed on the Indonesia Stock Exchange during 2018 – 2020. This study used a sample of 66 manufacturing companies after going through a selection process using purposive sampling. The data obtained was processed using Eviews 12.0 and Microsoft Excel. The result of this study indicate that profitability has an influence on intellectual capital. Board size have a negative influence on intellectual capital and institutional ownership have no effect of intellectual capital.